2012
DOI: 10.3389/fnhum.2012.00339
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic BOLD functional connectivity in humans and its electrophysiological correlates

Abstract: Neural oscillations subserve many human perceptual and cognitive operations. Accordingly, brain functional connectivity is not static in time, but fluctuates dynamically following the synchronization and desynchronization of neural populations. This dynamic functional connectivity has recently been demonstrated in spontaneous fluctuations of the Blood Oxygen Level-Dependent (BOLD) signal, measured with functional Magnetic Resonance Imaging (fMRI). We analyzed temporal fluctuations in BOLD connectivity and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
282
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(300 citation statements)
references
References 89 publications
17
282
1
Order By: Relevance
“…Similarly, it may be that resting-state functional connectivity is influenced not only by stable trait-like characteristics, but also by mental state, food or caffeine intake, daily exercise routines, awake-sleep patterns, seasonal change, and circadian and diurnal rhythms, which are more likely to be different when the scans are months apart than within the same session. Such a dependence of rs-fcMRI on mental state has been observed following a task stimulus (Grigg and Grady, 2010;Lewis et al, 2009;Stevens et al, 2010), when subjects were in different moods or emotional states (Eryilmaz et al, 2011), and with differences in vigilance (Tagliazucchi et al, 2012;Wong et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, it may be that resting-state functional connectivity is influenced not only by stable trait-like characteristics, but also by mental state, food or caffeine intake, daily exercise routines, awake-sleep patterns, seasonal change, and circadian and diurnal rhythms, which are more likely to be different when the scans are months apart than within the same session. Such a dependence of rs-fcMRI on mental state has been observed following a task stimulus (Grigg and Grady, 2010;Lewis et al, 2009;Stevens et al, 2010), when subjects were in different moods or emotional states (Eryilmaz et al, 2011), and with differences in vigilance (Tagliazucchi et al, 2012;Wong et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…However, the appearance of time-varying connectivity can also arise in signals that share no temporal information, complicating the interpretation of dynamic functional connectivity studies (Handwerker et al, 2012;Keilholz et al, 2013). A few labs have begun utilizing simultaneous imaging and electrophysiological recording to elucidate the neural basis of the networks and their variability in animals (Magri et al, 2012;Pan et al, 2011Pan et al, , 2013Scholvinck et al, 2010;Shmuel and Leopold, 2008;Thompson et al, 2013aThompson et al, , 2013b and in humans (Chang et al, 2013;Tagliazucchi et al, 2012;Wu et al, 2010). In this article, we review findings that link changes in electrically recorded brain states to changes in the networks obtained with rsMRI and discuss some of the challenges inherent in the interpretation of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic behavior has been observed in awake and sleeping humans (5-8), as well as in anesthetized animals (9, 10). Several studies involving simultaneous fMRI and electrophysiological recordings have suggested that FC dynamics may be driven by neurophysiological sources rather than noise (6,11,12). Furthermore, FC dynamics exhibit rich spatiotemporal structure.…”
mentioning
confidence: 99%